2020
DOI: 10.1002/brb3.1568
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in the progression of manic symptoms during acute hospitalization: A prospective pilot study

Abstract: Objectives Acute mania is a serious medical condition that impacts men and women equally. Longtime presentation of manic symptoms is sex‐dependent; however, little is known about acute symptoms of mania. The objective of this study is to track and compare acute manic symptoms for sex differences during inpatient hospitalization. Methods All patients with bipolar mania admitted to a large university hospital between January and October 2017 were invited to participate in this longitudinal naturalistic follow‐up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 80 publications
(122 reference statements)
0
9
0
Order By: Relevance
“…There were 24 studies reporting data on the point prevalence of psychotic symptoms in BD. For an overview of included studies, see online Supplementay Material 5: Studies included in the meta-analyses of the point prevalence of psychotic symptoms in bipolar disorders (Abulseoud et al, 2020 ; Asaad et al, 2014 ; Azorin, Adida, & Belzeaux, 2015 ; Azorin, Akiskal, & Hantouche, 2006 ; Basterreche et al, 2008 ; Benazzi, 2001 ; Bonnin et al, 2015 ; Caldieraro et al, 2017 ; Carroll, Vohs, O'Donnell, Shekhar, & Hetrick, 2007 ; Ciapparelli et al, 2001 ; Fiedorowicz et al, 2011 ; Goldberg & Harrow, 2004 ; Guven, Kesebir, Demirer, & Bilici, 2015 ; Kessing, 2004 ; Kessing, Jensen, & Christensen, 2008 ; Levy & Weiss, 2010 ; Lindenmayer, Bossie, Kujawa, Zhu, & Canuso, 2008 ; Lundin, Bartolomeo, O'Donnell, & Hetrick, 2018 ; Novis et al, 2014 ; Reddy, Meyer, Wittlin, Miller, & Weinstock, 2017 ; Salem et al, 2019 ; Samalin et al, 2014 ; Schwartzmann et al, 2007 ; Yildiz, Guleryuz, Ankerst, Ongur, & Renshaw, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were 24 studies reporting data on the point prevalence of psychotic symptoms in BD. For an overview of included studies, see online Supplementay Material 5: Studies included in the meta-analyses of the point prevalence of psychotic symptoms in bipolar disorders (Abulseoud et al, 2020 ; Asaad et al, 2014 ; Azorin, Adida, & Belzeaux, 2015 ; Azorin, Akiskal, & Hantouche, 2006 ; Basterreche et al, 2008 ; Benazzi, 2001 ; Bonnin et al, 2015 ; Caldieraro et al, 2017 ; Carroll, Vohs, O'Donnell, Shekhar, & Hetrick, 2007 ; Ciapparelli et al, 2001 ; Fiedorowicz et al, 2011 ; Goldberg & Harrow, 2004 ; Guven, Kesebir, Demirer, & Bilici, 2015 ; Kessing, 2004 ; Kessing, Jensen, & Christensen, 2008 ; Levy & Weiss, 2010 ; Lindenmayer, Bossie, Kujawa, Zhu, & Canuso, 2008 ; Lundin, Bartolomeo, O'Donnell, & Hetrick, 2018 ; Novis et al, 2014 ; Reddy, Meyer, Wittlin, Miller, & Weinstock, 2017 ; Salem et al, 2019 ; Samalin et al, 2014 ; Schwartzmann et al, 2007 ; Yildiz, Guleryuz, Ankerst, Ongur, & Renshaw, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…The pooled point prevalence for psychotic symptoms in the 20 studies using DSM BD diagnoses ( n = 4856) was 41.5% (95% CI 32–52) (Abulseoud et al, 2020 ; Asaad et al, 2014 ; Azorin et al, 2006 , 2015 ; Basterreche et al, 2008 ; Benazzi, 2001 ; Bonnin et al, 2015 ; Caldieraro et al, 2017 ; Carroll et al, 2007 ; Ciapparelli et al, 2001 ; Guven et al, 2015 ; Levy & Weiss, 2010 ; Lindenmayer et al, 2008 ; Lundin et al, 2018 ; Novis et al, 2014 ; Reddy et al, 2017 ; Salem et al, 2019 ; Samalin et al, 2014 ; Schwartzmann et al, 2007 ; Yildiz et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who had weaker awareness of their own symptoms were more likely to have worse behaviors [32]. Abulseoud et al reported that male patients with more disruptive and aggressive behaviors had less insight compared to female ones [33]. Volavka et al indicated that treatment non-adherence greatly increased the risk of risky behavior, and poor insight as well as hostility was associated with nonadherence [24].…”
Section: Discussionmentioning
confidence: 99%